Letter to the editor: reevaluating perioperative risks of intracranial infection after duraplasty in Chiari malformation type I - Brijesh Sathian; Hanadi Al Hamad (Egyptian Journal of Neurosurgery)
Abstract This letter addresses the article “Perioperative Risks of Intracranial Infection after duraplasty in Chiari Malformation Type I” by Balawi and Liao, published in the Egyptian Journal of Neurosurgery (Egypt J Neurosurg 40:58, 2025). While acknowledging the significance of the authors’ findings on risk factors for post-operative intracranial infections, we highlight the omission of critical variables such as the patient microbiome, recent advancements in surgical techniques, and post-operative care strategies. We argue that a more comprehensive understanding of infection risks should include these factors, as they play a crucial role in improving surgical outcomes.